Antifungal activity of Myriocin on clinically relevant Aspergillus fumigatus strains producing biofilm. Issue 1 (December 2015) - Perdoni, Federica; Signorelli, Paola; Cirasola, Daniela; Caretti, Anna; Galimberti, Valentina; Biggiogera, Marco; Gasco, Paolo; Musicanti, Claudia; Morace, Giulia; Borghi, Elisa
Abstract Background The human pathogenic moldAspergillus fumigatus is able to form a complex biofilm embedded in extracellular matrix. Biofilms confer antimicrobial resistance and it is well known that aspergillosis is often refractory to the conventional antifungal therapy. The treatment of biofilm-related infections poses a significant clinical challenge on a daily basis, promoting the search for new therapeutic agents. Our aim was to exploit the modulation of sphingolipid mediators as new therapeutic target to overcome antifungal resistance in biofilm-related infections. Results Antifungal susceptibility testing was performed on 20 clinical isolates ofAspergillus fumigatus and one reference strain (A. fumigatus Af293) according the EUCAST protocol. Sessile MICs were assessed on 24-h preformed-biofilm by means of XTT-reduction assay. Myriocin (0.25–64 mg/L), a commercial sphingolipid synthesis inhibitor, was used. The MEC50 value (mg/L) of Myriocin was 8 (range 4–16) for both planktonic and sessile cells. Drug-induced morphological alterations were analyzed by optical and electron microscopy (TEM) on 24h preformedA. fumigatus Af293 biofilms. An evident hyphal damage, resulting in short, stubby, and highly branched hyphae was observed by optical microscopy. At 24h, TEM studies showed important morphological alterations, such as invaginations of the cell membrane, modification in the vacuolar system and presence of multilamellar bodies, in some cases within vacuoles. Conclusions The direct antifungal activity, observed on both planktonic and sessile fungi, suggests that inhibition of sphingolipid synthesis could represent a new target to fight biofilm-relatedA. fumigatus resistance.